Geopolitical risk and corporate maturity mismatch - Wang, Man; Wang, Xueting (Journal of Financial Stability, 2025)
This paper explores how geopolitical risk affects corporate maturity mismatch using a sample of Chinese listed corporations. We find that geopolitical risk significantly exacerbates corporate maturity mismatch. Specifically, GPR increases corporate long-term investment and short-term debt, while decreasing corporate short-term investment and long-term debt. Further, the impact of GPR is amplified by R&D investment, industry competitiveness, and financial constraint, but weakened by corporate credit quality. The results of the mechanism test suggest that geopolitical risk exacerbates corporate maturity mismatch by increasing corporate information asymmetry and default risk. Additionally, we find that the impact of GPR on corporate maturity mismatch exhibits industry heterogeneity, and the positive effect of geopolitical risk on corporate maturity mismatch is more significant for high-growth corporations, non-state-owned corporations, small corporations, multinational corporations, and capital-intensive corporations. Finally, based on the extended Fama-French models, we construct two firm-level GPR indicators and the results indicate that individual GPR exacerbates maturity mismatch. Our paper enriches the research on the factors affecting maturity mismatch and helps corporations better manage operational and uncertainty risks.